Sustained disease remission and inhibition of radiographic progression in methotrexate-naive patients with rheumatoid arthritis and poor prognostic factors treated with abatacept: 2-year outcomes. Issue 11 (6th August 2011) - Bathon, J; Robles, M; Ximenes, A C; Nayiager, S; Wollenhaupt, J; Durez, P; Gomez-Reino, J; Grassi, W; Haraoui, B; Shergy, W; Park, S-H; Genant, H; et al.
Abstract : Objective: To assess the efficacy and safety of abatacept plus methotrexate versus methotrexate alone in early erosive rheumatoid arthritis (RA). Methods: The AGREE was a 2-year phase IIIb multinational study in early (≤2 years) RA. During the double-blind period (year 1), patients were randomly assigned 1:1 to receive abatacept+methotrexate or methotrexate alone; all patients received open-label abatacept+methotrexate during year 2. Clinical outcomes assessed included 28-joint disease activity score (DAS28) defined remission, low disease activity score (LDAS), American College of Rheumatology (ACR) responses and physical function. Radiographic outcomes were assessed using the Genant-modified Sharp total score (TS). Safety was monitored throughout. Results: Of the 459 patients completing year 1, 433 patients (94.3%) completed year 2. DAS28-defined remission, LDAS, ACR and physical function were sustained through year 2 in the original abatacept+methotrexate group, with 55.2% in remission at 2 years. Upon introduction of abatacept in the methotrexate-alone group, additional patients achieved DAS28-defined remission (44.5% vs 26.9%), LDAS (60.4% vs 43.2%) and improved ACR 70 (49.8% vs 31.7%) for year 2 versus year 1. Less radiographic progression was observed at 2 years in the original abatacept+methotrexate group than the methotrexate-alone group (change in TS 0.84 vs 1.75, p<0.001). No new safety issues were seen. Similar rates of serious adverse events, serious infections and autoimmune events were observed in years 1 and 2. Conclusions: The AGREE trial was the first to examine the impact of T-cell co-stimulation modulation with abatacept in patients with early erosive RA. Early treatment with abatacept+methotrexate resulted in greater sustainable clinical, functional and radiographic benefits than methotrexate alone, with acceptable safety and tolerability. Trial Registration: NCT00122382